EVALUASI PROGRAM PENGEMBANGAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DAN MUTU PENDIDIKAN - Amani, Khoirul (Academy of Education Journal, 2023)
This study aims to evaluate the effectiveness of principals' leadership development programs in improving teacher performance and education quality. Through a qualitative approach with a case study method, we investigated the impact of the principal leadership development program in several schools. Data were collected through participatory observation, in-depth interviews, and analysis of program-related documents at senior high schools. The results show that the leadership development program significantly impacts teacher performance and education quality. Principals who participated in the program experienced improvements in leadership skills strengthened inter-staff relationships and facilitated innovation in learning. Contextual factors, such as school support and staff commitment, also played an essential role in the program's success. This research highlights the importance of a sustainable approach to principal leadership development and emphasizes the need for strong policy support to underpin these efforts. The results of this study make an essential contribution to understanding the role and impact of principal leadership development programs in improving education quality.